GAMBARAN GANGGUAN OTONOM PADA PASIEN PARKINSON DI RSUPN CIPTO MANGUNKUSUMO DAN RSUP FATMAWATI - Maria Arasen, Eva Dewati, Freddy Sitorus, Herqutanto (NEURONA, 2013)
INTRODUCTION AUTONOMIC SYMPTOMS ARE QUITE OFTEN REPORTED BY PARKINSONS DISEASE PATIENTS COMPRISE GASTROINTESTINAL URINARY CARDIOVASCULAR SEXUAL AND THERMOREGULATION SYMPTOMPS SCOPAAUT SCALE FOR OUTCOMES IN PARKINSONS DISEASE FOR AUTONOMIC SYMPTOMS QUESTIONNAIRE CAN DETECT AUTONOMIC DYSFUNCTIONS AND HAD BEEN VALIDATED IN INDONESIAN LANGUAGE BUT IT NEVER